Impact assessment of CCAFS support to the 7th Five Year Plan in Bangladesh - Muzammil, Maliha (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
The CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) addresses the challenges of climate change and food security by mobilizing CGIAR and partner science and expertise to achieve positive change through evidence-based policy impacts with respect to climate-smart agriculture (CSA), food systems, and landscapes under climate change (CAS Secretariat, 2020). The future scenarios project under the theme uses multi-stakeholder regional and national scenarios to explore key socio-economic and uncertainties for food security, environments and livelihoods under climate change through integrated qualitative-quantitative scenarios describing futures up to 2050. The CCAFS South Asia (SA) Regional Scenarios Coordinator along with the Future Scenarios Project Team has been supporting the Government of Bangladesh (GoB) with successful policy guidance by using participatory scenarios for planning, training and capacity building from 2014. Since then, the SA Scenarios Coordinator has worked on building long-standing, effective collaborations with the government, civil society and academic stakeholders for strategic planning and research to explore the feasibility of strategies, plans and policies toward improved food security, environments and livelihoods under different socio-economic and governance conditions. The CCAFS future scenarios work has impacted the key economic development policy of Bangladesh – the Five Year Plan (FYP).